2015
DOI: 10.1016/j.stemcr.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Maturation of Human Stem Cell-Derived Pancreatic Progenitor Cells into Insulin-Secreting Cells in Immunodeficient Rats Relative to Mice

Abstract: SummaryPluripotent human embryonic stem cells (hESCs) are a potential source of transplantable cells for treating patients with diabetes. To investigate the impact of the host recipient on hESC-derived pancreatic progenitor cell maturation, cells were transplanted into immunodeficient SCID-beige mice or nude rats. Following the transplant, basal human C-peptide levels were consistently higher in mice compared with rats, but only rats showed robust meal- and glucose-responsive human C-peptide secretion by 19–21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 43 publications
3
59
1
1
Order By: Relevance
“…), examining protein expression in individual insulin + cells by immunofluorescent staining is a more accurate assessment of the hESCderived b-cell phenotype. The various lines of evidence pointing to a b-cell deficiency in hypothyroid mice are consistent with our previous observations in nude rats implanted with hESC-derived progenitor cells (16). Interestingly, nude rats had significantly higher circulating T3 levels than SCID-beige mice and also had improved glucosestimulated human insulin secretion, a higher proportion of insulin-to-glucagon immunoreactivity in grafts, and more consistent nuclear MAFA expression in hESC-derived b-cells than SCID-beige mice (16).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…), examining protein expression in individual insulin + cells by immunofluorescent staining is a more accurate assessment of the hESCderived b-cell phenotype. The various lines of evidence pointing to a b-cell deficiency in hypothyroid mice are consistent with our previous observations in nude rats implanted with hESC-derived progenitor cells (16). Interestingly, nude rats had significantly higher circulating T3 levels than SCID-beige mice and also had improved glucosestimulated human insulin secretion, a higher proportion of insulin-to-glucagon immunoreactivity in grafts, and more consistent nuclear MAFA expression in hESC-derived b-cells than SCID-beige mice (16).…”
Section: Discussionsupporting
confidence: 91%
“…The various lines of evidence pointing to a b-cell deficiency in hypothyroid mice are consistent with our previous observations in nude rats implanted with hESC-derived progenitor cells (16). Interestingly, nude rats had significantly higher circulating T3 levels than SCID-beige mice and also had improved glucosestimulated human insulin secretion, a higher proportion of insulin-to-glucagon immunoreactivity in grafts, and more consistent nuclear MAFA expression in hESC-derived b-cells than SCID-beige mice (16). Neonatal rats with hypothyroidism also exhibited decreased islet Mafa expression (12), which is consistent with our findings and suggests a potential role for thyroid hormone in regulating b-cell maturation.…”
Section: Discussionsupporting
confidence: 91%
“…However, it must be kept in mind that these cells have not yet been evaluated in large animal models or in humans. In fact, it has been shown that there are species differences even between mice and rats regarding the differentiation and engraftment of insulin-producing cells derived from hESCs (31). From a safety point of view, the cells therefore initially need to be transplanted into a site where they can be radically retrieved if needed.…”
Section: Transplantation Of Insulin-producing Cells Derived From Stemmentioning
confidence: 99%
“…Subsequently, studies reported enrichment of cells expressing high levels of NKX6.1 from the pancreatic progenitor cell population accelerated in viv o maturation period [34]. Furthermore, transplantation of stem-cell derived endocrine cells into rats relative to mice hastened the in vivo maturation process [35]. However, several unanswered questions remain in the context of maturation of pancreatic progenitors in the rodent system and the relevance of the in vivo maturation process when translating the approach to human clinical trials.…”
Section: Generating Beta Cells From Es Cells or From Ips Cellsmentioning
confidence: 99%